Enhancing Learning Outcomes in Vocational Animation Education: A Quasi-Experimental Study of Kahoot-Assisted Game-Based Learning in Indonesia - Aris Budianto; Dinta Sannyaturohmah; Basori Basori (Journal of Informatics and Vocational Education, 2025)
Student disengagement during theory-based instruction in vocational high schools remains a critical pedagogical challenge. Game-based learning (GBL) has emerged as an innovative approach to improve student engagement and achievement, particularly in vocational education. This study aimed to examine the difference in learning outcomes and the effectiveness of the Kahoot-assisted GBL model compared to conventional learning in the 2D Animation subject.  A quasi-experimental pretest-posttest control group design was employed. Sixty-one grade XI Multimedia students at a vocational high school in Surakarta were selected through cluster random sampling (experimental n=30, control n=31). Data were collected via validated achievement tests and analyzed using an independent sample t-test and normalized gain index. Results showed a significant difference in learning outcomes (t=5.548, p=0.000<0.05). The normalized gain score of the experimental class (g=0.52, medium category) was significantly higher than the control class (g=0.20, low category). Kahoot-assisted GBL is more effective than conventional learning in improving student learning outcomes in 2D Animation. These findings offer evidence-based guidance for vocational educators seeking to enhance theory-based learning through gamified digital tools. This study contributes to the limited body of evidence on gamified learning in vocational multimedia education within the developing country context.